Correlation between comorbidities, age group and Rock Index in Covid-19 infected adults in a South American Hospital (Boletin Médico de Postgrado, 2024)
The presence of comorbidities and longevity is associated with worse outcomes in patients with COVID-19 infection. A retrospective study of 306 adults infected with SARS-CoV-2 was conducted to evaluate the role of the ROX index and comorbidities according to age group as predictors of respiratory failure and mortality. In the inferential statistical analysis, OR odds ratios with confidence intervals greater than 95% were used as measures of association. Qualitative variables were evaluated using the Chi-square test or Fisher's exact test, and in the case of numerical or quantitative variables, the Student's t-test or Mann-Whitney test was used. The correlation between comorbidities and ROX index and cumulative mortality of the patients showed that in the group with less than one comorbidity n 89/306 (29.08%) the ROX index value was 5.42 (SD: 3.54-6.5) with a mortality of 9%. In the group between 1 to 4 comorbidities n 167/306 (54.57%), the ROX index value was 4.2 (SD: 3.1-5.3) with a cumulative mortality of 21%. Finally, the group with more than 4 comorbidities n 50/306 (16.33%) presented the lowest ROX index (2.88; SD: 2.43-3.33) and showed the highest mortality (64%). The present study showed a correlation between the ROX index and older age groups, showing a higher mortality in those older than 70 years and a higher rate of comorbidities and lower ROX.